Current epidemiology and antimicrobial resistance data for bacterial bloodstream infections in patients with hematologic malignancies: an Italian multicentre prospective survey. (April 2015) - Trecarichi, E.M.; Pagano, L.; Candoni, A.; Pastore, D.; Cattaneo, C.; Fanci, R.; Nosari, A.; Caira, M.; Spadea, A.; Busca, A.; Vianelli, N.; Tumbarello, M.; et al.
Abstract: A prospective cohort study was conducted in nine hematology wards at tertiary care centres or at university hospitals located throughout Italy from January 2009 to December 2012. All of the cases of bacterial bloodstream infection (BBSI) occurring in adult patients with hematologic malignancies were included. A total of 668 bacterial isolates were recovered in 575 BBSI episodes. Overall, the susceptibility rates of Gram-negative bacteria were 59.1% to ceftazidime, 20.1% to ciprofloxacin, 79.1% to meropenem, 85.2% to amikacin, 69.2% to gentamicin and 69.8% to piperacillin/tazobactam. Resistance to third-generation cephalosporins was found in 98/265 (36.9%) of Enterobacteriaceae isolates. Among Klebsiella pneumoniae strains, 15/43 (34.9%) were resistant to carbapenems. Of 66 Pseudomonas aeruginosa isolates, 46 (69.7%) were multidrug resistant. Overall, the susceptibility rates of Gram-positive bacteria were 97.4% to vancomycin and 94.2% to teicoplanin. Among the monomicrobial cases of BBSI, the 21-day mortality rate was significantly higher for those caused by Gram-negative bacteria compared to those caused by Gram-positive bacteria (47/278, 16.9% vs. 12/212, 5.6%; p < 0.001). Among Gram-negative bacteria, the mortality rate was significantly higher for BBSI caused by K. pneumoniae, P. aeruginosa, and Acinetobacter baumannii. Our results confirm the recently reported shift of prevalence from Gram-positive to Gram-negative bacteria as causative agents of BBSIs among patients with hematologic malignancies and highlight a worrisome increasing frequency in antimicrobial resistance among Gram-negative bacteria.